Sense-making as digitalization. Measuring, counting, and calculating as fundamental processes of digital ‘Bildung’ - Manhart, Sebastian (Frontiers in Sociology, 2025)
The article provides a clarification of the concept of digitalization, bringing together its two dimensions: electronic-physical information transformation and the social aspect of connection through the sense-making and creation of meaning via numbers. This is done both conceptually and by presenting the historical development of this socially complex synthesis of causality, sense-making and meaning. Fundamental aspects of social change from communication to information processing, from facts to data, from true nature to virtual possibility, from face-to-face sociality to digital habituation, from human to digital intelligence are presented in their development using historical examples. The focus is on the practices of counting, calculating, and measuring, whose gradual differentiation from communication enables the unlikely process of social implementation of an operationally meaningful but at the same time completely reference-less (digital) semiosis. The analysis of these specifically modern organizational and pedagogical developments as a prerequisite for digitization allows conclusions to be drawn about some aspects of digital subjectivity and society in the age of artificial intelligence.